Structural characteristics of dentofacial deformities in patients with diagnosed temporomandibular disorders - Semchyshyn, Я. О.; Rybert, Ю. О. (Actual Dentistry, 2024)
Purpose of the study. To determine the structure and nature of malocclusions and secondary deformities of occlusion in patients with diagnosed temporomandibular disorders. Materials and methods. 79 patients aged 14 to 50 years with temporomandibular disorders and dentofacial deformities were examined, including 20 (25.3%) men and 59 (74.7%) women. Attention is drawn to the significant predominance of women (almost three times) against men in almost all age groups. Research results. An analysis was made of what kind of dentofacial deformities patients with temporomandibular disorders addressed. For this purpose, patients are grouped according to the following pathologies: malocclusion, secondary occlusal deformities ,malocclusion+ secondary occlusal deformities, as well as the group that completed orthodontic treatment. It was determined that the group of patients with malocclusion significantly exceeds all other groups of the study- 72.15% (men 22.8%, women 49.4%). Secondary occlusal deformities were diagnosed only among women (7.6%). Combined deformities (malocclusion + secondary occlusion deformities) were diagnosed in 12.65% (2.5% of men, 10.1% of women). In the group of patients with completed orthodontic treatment, the indicator is 7.6%, of which only women. Conclusions. An important factor in the study is the determination of the fact of the existing combination of temporomandibular disorders and dentofacial deformities, which require the development of special approaches and sequences of actions for the treatment of such patients, as indicated by other researchers.